(untitled) (Research, Society and Development, 2021)
Introduction: The health professional who assists women who breastfeed needs to be able to develop actions that promote this very important practice. The influence of the health team becomes important, especially the nurse in exclusive breastfeeding and its impact on the health of the mother-baby binomial. in the face of the weaknesses found in nursing actions, it is necessary, strategies to promote the indispensable attention to the subject. This aptitude is based on pillars such as the bond and understanding about the topic. Objective: reflect on the importance of health education as tool for greater adherence to breastfeeding exclusive in the family health strategy. Methodology: study with a qualitative approach, with an integrative literature review, performing a search in virtual databases. Results: Conclusion: It was concluded that education in health is an extremely effective tool. Results: Conclusion: It was concluded that education in health is an extremely effective tool for the promotion of breastfeeding and that professionals working in the strategy family health, in particular the qualified nurse, have the ability to motivate mothers and teach families on the practice and benefits of breastfeeding.